Shelf life Characteristics of Pangasianodon hypophthalmus Fillets Treated with Moringa oleifera (Lam) Leaf extract - S. S., Greeshma; K., Sarika.; E. R., Priya.; R. G. Kumar, Lekshmi.; Joseph, Toms. C.; Pandey, M. C.; Prasad, M. M. (Fishery Technology, 2019)
Effect of dip treatment in Moringa oleifera (Lam) leaf extract (MOL) on the quality and shelf life of vacuum packed Pangasianodon hypophthalmus fillets was evaluated during chilled storage at 2 Â± 1Â°C. The control (untreated) and treated groups with 5% (v/v) and 10% (v/v) Moringa oleifera leaf extract (MOL) were examined periodically at 0, 3, 6, 9, 12, 15, 18 days during chilled storage until rejection by sensory, physicochemical and microbiological methods. The study revealed that the Moringa oleifera extract is a good source of phenolic compounds with significant antioxidant potential. The total phenolic content was found to be 183.75 mg GAE 100 g-1. MOL was found to have high antioxidant potential. The pH and TBA values of control group were significantly higher (p<0.05) than treated groups. Among the treated samples 10% treatment showed the lowest value. Moringa oleifera leaf extract was also found to have strong antimicrobial potential which could retain the quality attributes of fillets during the storage time. The dip treatment with 5 and 10% MOL improved the shelf life of fillets by 6 days compared to control under vacuum packed condition. In microbiological view point this treatment can be effectively used as a safe biopreservative to extend the shelf life of vacuum packed pangasius fillets under chilled condition without any adverse effect on the sensory acceptance of the treated fillets.